"Well they would say that, wouldn't they!": Overcoming the most dangerous attitude in the workplace. Issue 5 (11th July 2016) - Linacre, Simon
Abstract : Purpose: Reviews the latest management developments across the globe and pinpoints practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: What is cynicism? To the manager, it is a cancerous, evil flow of negativity that stops employees from getting on with the job they are paid to do; it is the holding back of a company on the rise; it is the contamination of enthusiastic, young employees with so-called wise words from more experienced members of staff. In short, it is nothing less than the almost willful sabotage of all the good things a company tries to do. Practical Implications: Provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.